2014
DOI: 10.11138/mltj/2014.4.1.052
|View full text |Cite
|
Sign up to set email alerts
|

Partnership between platelet-rich plasma and mesenchymal stem cells: in vitro experience

Abstract: SummaryWe aim to identify current in vitro research exploring platelet-rich plasma (PRP) effects in human Mesenchymal Stem Cells (MSCs) that may encourage or limit the clinical application of MSCs along with PRP. After a systematic search, we identified 57 in vitro studies, focused on optimization of MSC manufacturing, and expanding knowledge about how PRP modifies MSCs behavior for translational purposes. Influences of PRP on proliferation, migration, stemness, preservation of MSC immune-modulatory properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 71 publications
(38 reference statements)
1
52
0
1
Order By: Relevance
“…This therapy was possible because other researches have demonstrated the benefit of this kind of treatment in similar wounds [12,34,59]. At the same way, after several months of treatment, they could see completely incorporation of the 3D, this without side effects were seen.…”
Section: Introductionmentioning
confidence: 72%
“…This therapy was possible because other researches have demonstrated the benefit of this kind of treatment in similar wounds [12,34,59]. At the same way, after several months of treatment, they could see completely incorporation of the 3D, this without side effects were seen.…”
Section: Introductionmentioning
confidence: 72%
“…Although the limited supply of fresh platelets is a bottleneck when using human growth supplements to yield large‐scale cellular materials for both cell banking and cell‐based therapies, outdated platelets from human blood donors have recently been shown to be an efficient and reliable resource for producing PL (Glovinski et al, ). Human‐derived PL not only surpasses xenogeneic FBS in terms of bio‐safety but also excels in maintaining the potential of MSCs for proliferation, differentiation and immunomodulation (Chen & Liu, ; Rubio‐Azpeitia & Andia, ). In addition to replacing FBS, PL can be used to supplement culture medium and not only accelerate MSC proliferation but also reduce the time required to harvest the number of cells required for clinical use (Griffiths, Baraniak, Copland, Nerem, & McDevitt, ; Riordan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the effect of PL on tri‐lineage differentiation, discrepancies exist in the results and cell types of different studies. However, in most cases, if not all, PL at least does not interfere with the multipotency of MSCs and often results in an improved biological performance of the resultant cellular materials (Rubio‐Azpeitia & Andia, ). Moreover, MSCs expanded in PL‐supplemented culture medium exhibited preserved immune‐privileged capacities, such as the suppression of T cell proliferation and activation (Flemming et al, ); such features enabled these cells to be used for treating graft‐vs‐host disease in clinical trials (Introna et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Use of PRP was then anticipated to improve clinical outcome since it has been reported that PRP enhances MSC proliferation and chondrogenic differentiation [21][22][23] and could further improve cartilage regeneration.…”
Section: Discussionmentioning
confidence: 99%